Meaning of the Tagline “Selalu Ada Selalu Bisa" in Tokopedia Advertisements - Andary, Ria Wuri (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
This research aims to analyze the meaning of the tagline "Selalu Ada Selalu Bisa" in Tokopedia advertisements using Ferdinand de Saussure's semiotic approach. Advertising has a vital role in marketing communications, which shapes consumer perceptions of a brand, and a strong tagline can create and build a strong brand image. Tokopedia, the leading e-commerce platform in Indonesia, uses this tagline to emphasize the availability of products and services and the platform's ability to meet consumer needs. This research analyzes the signifier and signifies of the tagline to understand how meaning is formed. The tagline "Selalu Ada Selalu Bisa" reflects Tokopedia's commitment to consistently providing consumer needs and ensuring ease of access to their services. The analysis in this research shows that the meaning of the tagline at the denotative level describes availability and capability. In contrast, at the connotative level, the meaning develops into a symbol of trust, convenience, and consumer empowerment.